2017
DOI: 10.3389/fphar.2017.00285
|View full text |Cite
|
Sign up to set email alerts
|

FH535 Suppresses Osteosarcoma Growth In Vitro and Inhibits Wnt Signaling through Tankyrases

Abstract: Osteosarcoma (OS) is an aggressive primary bone tumor which exhibits aberrantly activated Wnt signaling. The canonical Wnt signaling cascade has been shown to drive cancer progression and metastasis through the activation of β-catenin. Hence, small molecule inhibitors of Wnt targets are being explored as primary or adjuvant chemotherapy. In this study, we have investigated the ability of FH535, an antagonist of Wnt signaling, to inhibit the growth of OS cells. We found that FH535 was cytotoxic in all OS cell l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 52 publications
0
12
0
Order By: Relevance
“…Therefore, the inhibition of the Wnt/β-catenin pathway can serve as a potential therapeutic approach for cancer (2931). FH535 is an inhibitor of β-catenin, which inhibits cyclin D1 and survivin and decreases the proliferation of human colorectal cancer cells, liver cancer stem cells, hepatocellular carcinoma cells and HepG2 cells (24,3234).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the inhibition of the Wnt/β-catenin pathway can serve as a potential therapeutic approach for cancer (2931). FH535 is an inhibitor of β-catenin, which inhibits cyclin D1 and survivin and decreases the proliferation of human colorectal cancer cells, liver cancer stem cells, hepatocellular carcinoma cells and HepG2 cells (24,3234).…”
Section: Discussionmentioning
confidence: 99%
“…We next investigated the effect of FH535, which is a synthetic small molecule that antagonizes the action of β-catenin/TCF/LEF transcription factors [ 37 , 65 ]. Our data suggest that FH535 attenuates β-catenin expression by 2-fold compared to untreated cells ( Figure 9E and 9F ).…”
Section: Resultsmentioning
confidence: 99%
“…In the wound healing experiment, the 20 µM concentration of FH535 significantly reduced migration at 8 and 12 hours [16]. Also, it has been reported that FH535 inhibits proliferation at concentrations of 0.1µM, 1µM, and 10µM in osteosarcoma cells [17]. The antiprolif-erative effect observed in hepatocellular carcinoma cells with the addition of FH535 at 50µM concentration is similar to our study, but the antiproliferative effect observed in colorectal cancer cells with the addition of FH535 at 10µM concentration was not noticed in HEC1A cells.…”
Section: Discussionmentioning
confidence: 99%